2022
DOI: 10.1017/gmh.2022.24
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and barriers for clinical mental health help-seeking in Bangladeshi university students: a cross-sectional study

Abstract: Background University and college students are vulnerable to developing depressive symptoms. People in low-income countries are disproportionately impacted by mental health problems, yet few studies examine routes to accessing clinical services. Examining motivation and barriers toward seeking clinical mental health services in university students in Bangladesh is important. Method Using a cross-sectional survey (n = 350), we assess the relationship between the constructs of autonomy, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The majority were from the United States, where 34 of the 44 studies were based [ 9 , 23 , 41 72 ]. The remainder from Australia [ 73 , 74 ], Brazil [ 75 , 76 ], China [ 77 ], Canada [ 78 ], Ethiopia [ 79 ], Bangladesh [ 28 ], and Italy [ 80 ]. A total of nineteen studies were samples of students from separate individual universities [ 43 , 46 , 48 – 55 , 67 , 68 , 70 , 73 , 75 – 77 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority were from the United States, where 34 of the 44 studies were based [ 9 , 23 , 41 72 ]. The remainder from Australia [ 73 , 74 ], Brazil [ 75 , 76 ], China [ 77 ], Canada [ 78 ], Ethiopia [ 79 ], Bangladesh [ 28 ], and Italy [ 80 ]. A total of nineteen studies were samples of students from separate individual universities [ 43 , 46 , 48 – 55 , 67 , 68 , 70 , 73 , 75 – 77 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of nineteen studies were samples of students from separate individual universities [ 43 , 46 , 48 – 55 , 67 , 68 , 70 , 73 , 75 – 77 , 79 , 80 ]. Whereas the remaining twenty-four were samples across multiple universities [ 9 , 20 , 23 , 28 , 41 , 44 , 45 , 47 , 56 59 , 61 – 66 , 69 , 71 , 72 , 74 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Asia, there is documented widespread stigma surrounding mental health; however, few studies have examined the Bangladeshi views on mental health. One study in a University student sample in Bangladesh found that stigma was not significantly associated with reduced utilization of clinical mental health services; however, it is essential to note that the sample had low levels of stigma overall (Sifat, Tasnim, et al, 2022b ). However, in a systematic review on this topic, it was found that a majority of the community does not recognize mental illness, that attitudes regarding treatment are negative, and that even those with mental illness do not see treatment as a priority (Hossain et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%